Natural environments in the urban context and gut microbiota in infants. (September 2020) - Nielsen, Charlene C.; Gascon, Mireia; Osornio-Vargas, Alvaro R.; Shier, Catherine; Guttman, David S.; Becker, Allan B.; Azad, Meghan B.; Sears, Malcolm R.; Lefebvre, Diana L.; Moraes, Theo J.; Turvey, Stuart E.; Subbarao, Padmaja; et al.
Highlights: Proximity to natural urban environments – their vegetation, soil or water – may be beneficial for early life microbiota. Tested influence of a natural environment within 500 m of a home residence on infant gut microbiota at age 4 months. Proximity to a natural environment plus pet ownership reduced microbial diversity of infants not breastfed. Notable changes in gut microbial composition included enrichment of Proteobacteria that are commonly found in vegetation. Abstract: The biodiversity hypothesis that contact with natural environments (e.g. native vegetation) and biodiversity, through the influence of environmental microbes, may be beneficial for human commensal microbiota has been insufficiently tested. We aimed to study the association between living near natural environments in the urban context, and gut microbiota diversity and composition in young infants. Based on data linkage between the unique Urban Primary Land and Vegetation Inventory (uPLVI) for the city of Edmonton and 355 infants in the CHILD Cohort Study, infant exposure to natural environments (any and specific types, yes/no) was determined within 500 m and 1000 m of their home residence. Gut microbiota composition and diversity at age 4 months was assessed in infant fecal samples. Adjusted for covariates, we observed a reduced odds of high microbial alpha-diversity in the gut of infants exposed to any natural environment within 500 m [Shannon index aOR (95%CI) = 0.63 (0.40, 0.98) and Simpson index = 0.63 (0.41, 0.98)]. In stratified analyses, these associations remained only among infants not breastfed or living with household pets. When doubly stratifying by these variables, the reduced likelihood of high alpha-diversity was present only among infants who were not breastfed and lived with household pets [9% of the study population, Shannon index = 0.07 (0.01, 0.49) and Simpson index = 0.11 (0.02, 0.66)]. Differences in beta-diversity was also seen (p = 0.04) with proximity to a nature space in not breastfed and pets-exposed infants. No associations were observed among infants who were fully formula-fed but without pets at home. When families and their pets had close access to a natural environment, Verrucomicrobiales colonization was reduced in the gut microbiota of formula-fed infants, the abundance of Clostridiales was depleted, whereas the abundance of Enterobacteriales was enriched. Our double-stratified results indicate that proximity to a natural environment plus pet ownership has the capacity to alter the gut microbiota of formula-fed infants. Further research is needed to replicate and better interpret these results, as well as to understand their health consequences.